Anogenital Distance as a Predictor of Dysmenorrhea - Nicko Pisceski Kusika Saputra; Noviardi; Nopianti Sonia; Dina Sartika; Syafira Nadisa (Nusantara Science and Technology Proceedings, 2022)
Most women experience menstrual pain (dysmenorrhea) before and during menstruation. The prevalence of dysmenorrhea in Indonesia reaches 64.25%, consisting of 54.89% primary dysmenorrhea and 9.36% secondary dysmenorrhea. The incidence of dysmenorrhea among women of reproductive age ranges from 45% - 95%. Primary dysmenorrhea is experienced by 60% - 75% of adolescents. Many risk factors for dysmenorrhea have been identified, one of which is the anatomy of the reproductive organs. Anogenital distance (AGD) is the distance from the midpoint of the anus to the clitoris. Intrauterine estrogen exposure causes a shortened AGD, so this is a predictor of endometriosis with symptoms of dysmenorrhea. This study aims to determine the difference between AGD in adolescents with dysmenorrhea and non-dysmenorrhea. The sample of this study was 93 students of the Faculty of Medicine, Riau University, Class of 2020 and 2021. The results showed that the average age of the respondents was 19 years. As many as 73% of respondents experienced dysmenorrhea. The median of AGD in the dysmenorrhea group was 0,33 and the non-dysmenorrhea group was 0.43. There was a significant difference in the mean AGD between the two groups. It can be concluded that the size of the AGD can be a predictor of dysmenorrhea.